Applicability and Effectiveness of the Legal Transactions on Using Electronic Money (E-Money) in the Disruption Era - Suwardi Suwardi (ADP Publisher, 2023)
Human activity encounters a density that is no less incredible in pursuing its needs and ambitions. Some people have attempted to conduct transactions in pair with the abundance of technological development activities, specifically by using electronic money. In this study, the author observes remarkable technological growth, which aims to understand the essence of e-money transactions and their efficacy. Additionally, how effective is the legal defense against e-money transactions? This study uses a normative or doctrinal research method by comparing the Law and the enlightening validity of reading books, texts, journals, print media, and other related information. This study demonstrates that the validity of electronic money transactions has done a lot, whereas the transaction encloses safeness, convenience, and time efficiency. However, there are also obstacles and challenges in it. For effectiveness, there is already a legal validation that controls it. At the same time, electronic money transactions must be protected for legal protection, where it contains elements of worth, which are benefits and time efficiency.